Beta Caryophyllene-Loaded Nanostructured Lipid Carriers for Topical Management of Skin Disorders: Statistical Optimization, In Vitro and Dermatokinetic Evaluation - Mohammed Ghazwani; Umme Hani; Mohammed H. Alqarni; Aftab Alam (Gels, 2023)
This work aimed to overcome the disadvantages of the oral administration of beta-caryophyllene and boost efficiency by developing a nanostructured lipid carrier for topical administration of the drug in skin disorders. The heat emulsification method was utilized to produce beta-caryophyllene-loaded nanostructured lipid carriers. The newly created formulation was examined for its particle size, entrapment efficiency, and zeta potential after being improved using the Box–Behnken Design. The chosen formulation underwent tests to determine its ex vivo skin retention, dermatokinetic, in vitro release, antioxidant, and confocal laser scanning microscopy study. The findings of the characterization of the nanostructured lipid carriers demonstrated that the particles had a spherical form and a size of 210.86 nm (0.263 polydispersity index). The entrapment efficiency was determined to be 86.74%, and the zeta potential was measured to be −26.97 mV. The in vitro release investigation showed that nanostructure lipid carriers were capable of releasing regulated amounts of beta-caryophyllene for up to 24 hrs. In comparison to the traditional gel formulation, the ex vivo investigation demonstrated a 1.94-fold increase in the skin’s capacity to retain the substance. According to the findings of the study, nanostructure lipid carriers loaded with beta-caryophyllene have the potential to be investigated for use as a topical administration method in skin disorders with enhanced skin retention and effectiveness.